Uji Aktivitas Antibakteri Minyak Atsiri Kulit Jeruk Pontianak (Citrus nobilis Lour. var. microcarpa) terhadap Bakteri Staphylococcus aureus dan Staphylococcus mutans - meri ropiqa; Ika Ristia Rahman; Hadi Kurniawan; Erwan kurnianto (Journal Syifa Sciences and Clinical Research, 2023)
Antibacterial is a substance that can inhibit the growth of bacteria and can kill bacteria that cause infection. Currently increasing resistance to antibiotics is an opportunity to utilize bioactive compounds from the diversity of plants in Indonesia, one of which is by utilizing Pontianak orange peels. Based on some literature, it is stated that essential oils from Pontianak orange peels can inhibit the growth of several types of bacteria. In this study, antibacterial tests were carried out on S.aureus and S.mutans bacteria. The essential oil of Pontianak orange peel was first tested for phytochemical screening and then an antibacterial test was carried out with several concentrations of 5%, 10%, 25%, and 50%, the antibacterial activity test was carried out using the disc diffusion method. The results of the phytochemical screening test showed that the essential oil of Pontianak orange peel contains flavonoids, saponins, and terpenoids. Furthermore, in testing the S.aerues bacteria, the essential oil of orange peel can have an inhibition zone with a range of 9-11 mm which is included in the strong antibacterial category, while in testing the inhibition of S. mutans bacteria, it is included in the moderate category, namely in the range of 7-10 mm. In the statistical test, there was no significant difference in the inhibition of S. mutans and S.aereus bacteria in inhibiting the growth of the orange peel essential oil as indicated by the diameter of the inhibition zone in the different treatment groups according to the concentration of orange peel essential oil.